Dynamic changes and correlation analysis of protease activities, texture and flavour compounds during fish fermentation (suanyu) using mixed culture (Enterococcus rivorum and Enterococcus lactis). (3rd March 2023) - Yuan, Li; Zhang, Qianqian; Zhao, Feng; Jin, Wengang; Shi, Tong; Xiong, Zhiyu; Gao, Ruichang
Summary: This research investigated the dynamic changes and correlations of protease activity, material texture and flavour compounds during the fermentation (13 days) of crucian ( Carassius auratus ). Mixed starter fermentation ( Enterococcus rivorum and Enterococcus lactis ) and natural fermentation were used for the study. Results showed that the protease activity, TCA‐soluble protein and flavour substances were increased with fermentation time and were higher in the mixed fermentation group. The results of relative odour activity value showed that some aldehydes played a major role in the flavour of the product, such as octanal, nonanal and (E)‐2‐nonenal. The correlation analysis showed that protease activity and material texture (hardness and chewiness) had a significantly positive correlation with many flavour compounds (octanal, nonanal, glutamic acid, etc. ). This work will provide a theoretical reference for the application of mixed starter cultures and for improving the quality of suanyu by increasing protease activity and changing the texture of the material. Abstract : Schematic of mixed fermentation and correlation analysis of suanyu.